2020
DOI: 10.4102/curationis.v43i1.2114
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of psychiatric patients with mood disorders who attended group therapy facilitated by professional psychiatric nurses

Abstract: Background: According to the World Health Organization (WHO), up to 25% of people worldwide will develop mental health disorders during their lifetime. Patients admitted to acute inpatient units for mood disorders experience emotional distress. Group therapy has the potential to foster the therapeutic change through specific therapeutic mechanisms. Psychiatric nurses working in inpatient units are in a unique position to offer group therapy.Objectives: Explore and describe stabilised acute psychiatric patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 14 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…The total number of participants across the studies was at least 192, as one study was unable to provide the exact number of individual participants (Pownell et al, 2023). Four studies comprising 36 participants (Chen et al, 2018;Messari & Hallam, 2003;Small et al, 2018;Visagie et al, 2020) reported ethnicity as follows: Chinese (n = 15), White British (n = 8), African (n = 4), Asian British (n = 2), Mixed descent (n = 2), White (n = 2), African-Caribbean (n = 1), Black African (n = 1) and White Irish (n = 1). In the remaining studies, ethnicity was either not reported (n = 8), reported as 'multiple ethnicities' (n = 1) or was unable to be determined as the ethnicity of participants who had completed qualitative feedback was not distinguished from participants who either did not complete treatment (n = 3) or were staff participants (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The total number of participants across the studies was at least 192, as one study was unable to provide the exact number of individual participants (Pownell et al, 2023). Four studies comprising 36 participants (Chen et al, 2018;Messari & Hallam, 2003;Small et al, 2018;Visagie et al, 2020) reported ethnicity as follows: Chinese (n = 15), White British (n = 8), African (n = 4), Asian British (n = 2), Mixed descent (n = 2), White (n = 2), African-Caribbean (n = 1), Black African (n = 1) and White Irish (n = 1). In the remaining studies, ethnicity was either not reported (n = 8), reported as 'multiple ethnicities' (n = 1) or was unable to be determined as the ethnicity of participants who had completed qualitative feedback was not distinguished from participants who either did not complete treatment (n = 3) or were staff participants (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…'Sometimes the class was in a little bit of chaos and I felt irritable towards the group members who were speaking loudly and dominating the group' (Chen et al, 2018) '[Ask facilitators to] silence annoying patients who disrupt the group, they ruin the whole emphasis of the message that the psychologist is trying to get across' (Pownell et al, 2023) Groups did not always feel safe for some participants (Fife et al, 2019), and speaking about difficult experiences in front of others could be anxiety-provoking (Visagie et al, 2020). Some participants commented on groups feeling uncomfortable when peers did not contribute (Harris et al, 2021;Radcliffe & Bird, 2016) or were explicitly disrespectful, for example, laughing inappropriately (Chen et al, 2018).…”
Section: Challenges Of Group Therapymentioning
confidence: 99%
See 3 more Smart Citations